Crystal growth and optical properties of Ce-doped (Y, Lu)AlO3 single crystal. (1st July 2022) - Horiai, Takahiko; Pejchal, Jan; Paterek, Juraj; Kucerkova, Romana; Yokota, Yuui; Yoshikawa, Akira; Nikl, Martin
Abstract: (Ce0.002 Y0.998− x Lu x )AlO3 ( x  = 0.000, 0.010, 0.100, 0.200) single crystals were grown and characterized to clarify the effects of Lu substitution in Ce:YAlO3 on its crystal structure, optical properties and thermal stability of Ce 3+ luminescence. The lattice constants of (Ce0.002 Y0.798 Lu0.200 )AlO3 were comparable to those of Ce:YAlO3, so the crystal structure was not significantly influenced by Lu substitution. Concerning the optical characterization, the absorption and emission spectra were almost the same regardless the amount of Lu substitution. This result is consistent with the assumption that the crystal field is not influenced by Lu substitution. The temperature dependences of the photoluminescence decay time showed that the quenching temperature ( T 50% ) tends to increase with the increasing Lu concentration. We conclude that the leading quenching mechanism is the thermally activated ionization which is suppressed by the Lu substitution in Ce:YAlO3 .